Influence of dietary protein levels and meal allocation on the biological performance of saline-tolerant tilapia (O. mossambicus x O. niloticus) Hybrid - Golingay, Cezarie Lagutin (2019.)
A 60-day feeding trial was conducted on saline-tolerant tilapia (O. mossambicus x O.niloticus) hybrid with initial mean body weight of 3.87 +_ 0.31g. Two diets were formulated to contain two levels of dietary protein (33% and 37%) that were given twice daily at different meal allocations (MA A: 30% AM;70%PM and MA B: 70%AM;30%PM). The survival was high at 97%-99%, Results of the feeding trial suggested that weight gain and specific growth rate were significantly (p <0.05) influenced by the detary protein level and meal allocation. Regardless of the meal allocation, protein efficiency ratio was significantly (p <0.05) higher when 33% CP diet was given. Proximate body composition (crude protein and crude lipid) were significantly (p<0.05) affected by the dietary protein level. The fish has increased muscle protein and decreased lipid content when given with 37% CP diet. Interaction of dietary protein levels and meal allocation was only significant (p<0.05) on the lipase activity of the fish. Fatty acid analysis revealed that regardless of the meal allocation, linoleic acid (18:2n-6) and total n-6 PUFAs were higher when 33% CP diet was offered. The interaction of the factors was significant only on the linoleic acid (18:3n-3) and was found to be highest when 33% CP diet was given at MA A. Interaction of the factors was significant on the visceral fat cells of the fish, being significantly (p<0.05) larger when 33% CP diet was given at higher meal allocation during the late afternoon. In the light of the findings derived from thid study, the high survival of saline-tilapia hybrid at 37 ppt confirms its potential use for brackish and seawater culture. The study also highlights the significance of dietary protein levels and meal allocation on the biological performance of saline-tilapia hybrid..
Thesis - M.S. Fisheries - Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas.
Keywords: Cage culture; Dietary protein levels; Feeds and feeding; Meal allocation; Tilapia; Oreochromis mossambicus; Oreochromis niloticus